2014
DOI: 10.1007/s00402-014-2000-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations of thoracic myelopathy

Abstract: This study elucidated symptoms specific to anatomical pathology or compressed segments in thoracic myelopathy. These relationships can be helpful in the initial investigation of thoracic diseases, although additional measures such as MRI or CT are necessary for definitive diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Diagnosis of thoracic myelopathy tends to be delayed because of its complex neurological manifestations and rarity. 2 Increased lower extremities muscle tone and deep tendon reflexes, and presence of pathological reflexes indicate myelopathy. However, these are more frequently recognised in, and associated with, cervical myelopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of thoracic myelopathy tends to be delayed because of its complex neurological manifestations and rarity. 2 Increased lower extremities muscle tone and deep tendon reflexes, and presence of pathological reflexes indicate myelopathy. However, these are more frequently recognised in, and associated with, cervical myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of thoracic myelopathy was established on clinical symptoms, physical examination, and imaging studies. Relevant clinical features included tightness around the trunk, numbness and sensory deficitis in the lower extremities, weakness in the lower extremities, altered proprioceptive sensation, 2,10 gait disturbance, and sphincter dysfunction. Other positive physical examinations consisted of increased lower extremities muscle tone and deep tendon reflexes, and presence of pathological reflexes.…”
Section: Patientsmentioning
confidence: 99%
“…Analysis of myelopathic gait can be found for patients with cervical myelopathy due to cervical spondylosis and/or OPLL who were able to autonomously ambulate before and after decompression surgery (27). Compared with cervical myelopathy, neurological deterioration in thoracic myelopathy is rather concentrated in the lower limbs: lower limb numbness and weakness and an unsteady gait (28). Post-operative motor paralysis was observed in more than 30% of thoracic patients who underwent surgery for OPLL, more than 20% of whom underwent additional surgery to achieve recovery (29).…”
Section: Introductionmentioning
confidence: 99%
“…TOLF can cause compression of corresponding spinal cord segments, numbness, and weakness in both lower limbs, abnormal gait, dyskinesia, sphincter dysfunction, and lower limb paraplegia. 1,2 With the popularization of large-scale imaging equipment and a deeper understanding of the disease, the number of clinical reports into TOLF has increased. [1][2][3][4] Epidemiological studies have shown that it is particularly prevalent in the Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 With the popularization of large-scale imaging equipment and a deeper understanding of the disease, the number of clinical reports into TOLF has increased. [1][2][3][4] Epidemiological studies have shown that it is particularly prevalent in the Asian population. 3,4 Conservative treatment is usually ineffective for TOLF, so surgical treatment is widely accepted as the best approach.…”
Section: Introductionmentioning
confidence: 99%